Prospect of Eco-Tourism in Upper-Humla: A Case Study of Namkha Rural Municipality - DC, Daman Dhoj (Academia Research Journal, 2025)
Tourism is one of the world’s largest and fastest-growing industries, contributing significantly to economic growth, cultural exchange, and environmental awareness. In Nepal, approximately 80% of tourism is linked to nature-based activities, positioning eco-tourism as a vital driver of sustainable development. This study examines the prospects of eco-tourism in Upper Humla, focusing on Namkha Rural Municipality, an area rich in natural beauty, biodiversity, and cultural heritage but constrained by remoteness and underdeveloped infrastructure. Employing a descriptive and exploratory research design, data were collected from 75 local residents and 15 tourists through structured questionnaires, interviews, focus group discussions, and field observations. Secondary data were sourced from government records, academic literature, and institutional reports. Findings reveal that Upper Humla offers exceptional eco-tourism resources, including iconic mountains such as Saipal and Panchmukhi Himal, sacred lakes like Selima, hot springs, Buddhist monasteries, Hindu temples, and rare medicinal plants. While locals emphasize cultural heritage as the key attraction, tourists prioritize trekking and natural scenery. The study identifies major constraints, including inadequate transportation and communication, limited accommodation, lack of promotion, and insufficient trained manpower. Respondents recommended infrastructural and superstructural development, awareness programs, local tourism policy formulation, and marketing initiatives. Positive impacts of tourism include employment generation and income growth, while potential negative effects involve cultural dilution and environmental degradation. The research concludes that eco-tourism in Upper Humla holds significant potential for rural development, poverty alleviation, and cultural preservation if pursued through integrated, community-based, and environmentally responsible strategies. Targeted investments, policy interventions, and sustainable management are essential to unlock this potential.